Critical reflections on the theory versus practice debate in communication for development - Manyozo, Linje (MedieKultur: Journal of media and communication research, 2016)
Even though the cliché ‘theory is practice’ registers in most communication for development debates, available evidence seems to suggest there is a growing chasm between the theory and practice of communication for development. This discussion argues that, with the increasing demand by governments and organisations for communication for development specialists, universities and training providers should rethink their graduate curricula. As course content, teaching methodologies and theoretical paradigms are revisited, trainers need to grill students on how the contestation of power is central to the application of communication in development. This paper advances two arguments. The first is that communication for development training has to begin listening to the innovative thinking that is shaping practice on the ground if the curriculum is to stay relevant. The second is that such programmes have forge strong linkages with development studies departments to ensure that students are well-grounded in development theory and practice.